A 424 and 448 GHz Receiver for Aircraft Contrail Observations - Andy Fung; Pekka Kangaslahti; William Chun; Joelle Cooperrider; Javier Bosch-Lluis; Joan Munoz-Martin; Mary Soria; Erika Hernandez; Alan Tanner; Omkar Pradhan; Willam Deal; Caitlyn Cooke; et al. (IEEE Journal of Microwaves)
Airplane produced contrail cirrus has a greenhouse effect in our atmosphere. It has an effect that is as much as or more than any other airplane emission such as airplane produced CO2 Karcher et al. 2018. With air traffic anticipated to increase into the future it is important to understand contrail cirrus formation. We present a new receiver instrument using the 424 GHz (O2) and 448 GHz (H2O) emission lines for thermal and humidity profiling that will provide data to model airplane contrail formation. Such an instrument can be used for guiding aircraft flight paths to reduce the development of contrail cirrus that can have an immediate greenhouse effect in our atmosphere.